An empirical analysis of credit-financed agribusiness investments and income poverty dynamics of rural women in Cameroon. Issue 1 (1st January 2020) - Kimengsi, Jude Ndzifon; Balgah, Roland Azibo; Buchenrieder, Gertrud; Silberberger, Magdalene; Batosor, Hene Pridedinorah
ABSTRACT: The link between microcredit and income poverty reduction for the poor is well established. However, contemporary empirical evidence remains mixed, especially among women beneficiaries. We use a purposive sample of 160 women from 80 microcredit groups of the Program for the Improvement of the Competitiveness of Family Agro Pastoral Farms (ACEFA) in Cameroon to assess the relationships between rural women's microcredit access and their income poverty dynamics. ACEFA's credit-plus group-lending approach offers extension services and trainings plus credit to women. Binary logistic regression results reveal that this model up-scales agribusinesses, increases incomes, and prevents "credit capture" by men. The model supports risk-taking behavior, enhances credit efficiency, and promotes successful agribusiness development better than standalone microcredit models.